Taxonomy and phylogeny of juncaceicola gen. nov. (Phaeosphaeriaceae, Pleosporinae, Pleosporales) - Danushka S. Tennakoon (2018)
© 2016 Adac. Tous droits réservés. In order to establish phylogenetic relationships and resolve a natural classification for species of Dothideomycetes, it is necessary to use multi-gene phylogeny as well as morphology. In this paper we introduce a novel genus, Juncaceicola collected from Italy, in the family Phaeosphaeriaceae, with three new species, Juncaceicola achilleae on dead twigs of Achillea millefolium, J. dactylidis on dead twigs of Dactylidis sp. and J. luzulae on dead herbaceous stems of Luzula nivea. Juncaceicola is characterized by globose to subglobose ascomata with a minute papilla, a peridium composed of pseudoparenchymatous cells arranged in a textura angularis to textura prismatica, cylindric-clavate asci with a short pedicel and yellowish brown, ellipsoidal to fusiform, 3-4-septate ascospores, with the second cell from the apex enlarged. Descriptions and illustrations for each novel taxon and a key for morphological character differences are provided. Combined analyses of ITS, LSU and SSU sequence data support the validity of the new species with high bootstrap support and the placement of Juncaceicola in Phaeosphaeriaceae. Phaeosphaeria alpina, P. oreochloae, P. padellana and P. typharum are also transferred to the new genus.